APPROACHES TO UNDERSTANDING THE PHENOMENON OF POLYSEMY (Academicia Globe: Inderscience Research, 2022)
The article provides an overview of approaches to understanding the phenomenon of polysemy, discusses the interpretation of the concept of lexico-semantic variant and its relationship with the concept of "meaning". The possibilities of an invariant approach to the organization of the meaning of a word are analyzed.